Facio-odontometric analysis in mass disaster victim identification - A novel approach - Rajkumari Sriraman; Monica Dev (Wolters Kluwer Medknow Publications, 2021)
Introduction: Forensic dentistry is an evolving field in legal medicine. In mass disasters, the co-mingled body parts can be misplaced; however, the intervention by dental experts can efficiently sort out the dispute. Understanding the fact that, rule of phi applies to all that exists in nature, in the present study, we aimed to correlate the Total Maxillary Arch Perimeter with the Total Body Height of an individual in cases scenarios where only the skull along with maxilla is the only leftover remains of the unidentified. Material and Methods: An observational study was designed involving ninety subjects comprising 45 males and 45 females of age 25 to 30 years for the following parameters. Total Body Height (TBH) was measured in centimetres using anthropometric rod. Total Facial Height (TFH) was then measured from nasion to gnathion using digital vernier caliper. Total Maxillary Arch Perimeter (TMAP) was measured from the maxillary arch model cast using digital vernier caliper. Results: The Total Maxillary Arch perimeter has significant positive correlation with Total Body Height as well as Total Facial Height of an individual. The regression equation was positively established for the prediction of Total Body Height from the known Total Maxillary Arch Perimeter as Total Body Height = 80.91762 + 0.718777 (Total Maxillary Arch Perimeter). Conclusion: The Total Maxillary Arch Perimeter can be used as a predictive tool in estimating the Total Body Height of the individual where the skeletal remains of the skull along with maxilla is only present.